Peran dan Variasi Instrumen Tes dalam Mengukur Ranah Kognitif Peserta Didik - Callysta Putri Adyra; Rahma Azahra; Zoya Julita Pratiwi; Anggun Rahma Andini; Wanda Wanda; Minarsi Minarsi; Yola Eka Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role and variation of test instruments in measuring students’ cognitive domain in the learning evaluation process. Using a literature review method, this study examines various scientific sources related to educational evaluation and cognitive assessment. The findings indicate that the cognitive domain includes thinking skills ranging from lower-order thinking skills (C1: Remembering, C2: Understanding) to higher-order thinking skills (C3: Applying, C4: Analyzing, C5: Evaluating, and C6: Creating) based on Bloom’s Taxonomy. Test instruments such as multiple-choice, essay, true-false, matching, and oral tests possess different characteristics, advantages, and limitations for assessing specific cognitive levels. Objective tests are considered effective for measuring lower-order thinking skills because they offer high reliability and objectivity, whereas essay tests are more appropriate for assessing higher-order thinking skills (HOTS). In addition, the quality of test instruments is influenced by validity, reliability, objectivity, difficulty level, and discrimination index. Therefore, the appropriate and varied use of test instruments is essential to obtain comprehensive and accurate measurements of students’ cognitive abilities and to support effective learning evaluation and instructional decision-making processes.